Biomass and elemental composition (C, N, H) of the periphytic community attached to Polygonum punctatum Ell. in a subtropical reservoir and its relationship to environmental factors - Taniwaki, Ricardo Hideo [UNESP]; Emilio Magrin, Albano Geraldo; Calijuri, Maria do Carmo; Carlos, Viviane Moschini [UNESP] (Asoc Espan Limnol-mislata, 2013)
The periphytic communities in Brazilian reservoirs have been studied widely due to their importance for the assimilation of nutrients and their role at the base of the food chain. The objective of the present work was to analyse the environmental variables that influence the development of periphytic communities attached to stalks of the aquatic macrophyte Polygonum punctatum Ell. Five sample collections were made during 2010 at two sites in the Itupararanga reservoir (Ibiua, Sao Paulo, Brazil). The macrophyte was collected, and the periphytic community attached to its stalks was scraped off with a brush and jets of distilled water. Using a PLS analysis, we observed that 94.3% of the variation in periphyton biomass could be explained by concentrations of nitrate, conductivity, dissolved oxygen, water clarity and dissolved inorganic phosphorous. According to the indices applied, in 2010 the biomass of the periphytic community in the reservoir was low and predominantly heterotrophic, and the concentration of carbon in the periphyton was lower than that found in previous studies of this community.
Keywords: Carbon; elemental composition; periphyton; reservoir